2014
DOI: 10.1038/jid.2013.396
|View full text |Cite
|
Sign up to set email alerts
|

siRNA Knockdown of Tissue Inhibitor of Metalloproteinase-1 in Keloid Fibroblasts Leads to Degradation of Collagen Type I

Abstract: Keloids are defined as overgrowths of scar tissue resulting from abnormal wound healing. They are characterized by excessive dermal deposition of thick, hyalinized collagen bundles resulting from an imbalance between the production and degradation of extracellular matrix (ECM) components. Matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) are two important regulators of ECM degradation and remodeling. To evaluate the role played by knockdown of TIMPs in keloid formation, we tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 44 publications
2
46
0
3
Order By: Relevance
“…However, some research has found that the expression of TIMP-1 is significantly higher in the scar tissue of patients with HS than in scar tissues of patients with normotrophic scars 32 . Moreover, targeting TIMP-1 using small interfering RNA has significant therapeutic potential as an approach to treating keloids 33 . In this study, the expression of TIMP-1 was significantly decreased with Endostar treatments, while the group that did not receive Endostar therapy showed over expression of TIMP-1.…”
Section: Discussionmentioning
confidence: 99%
“…However, some research has found that the expression of TIMP-1 is significantly higher in the scar tissue of patients with HS than in scar tissues of patients with normotrophic scars 32 . Moreover, targeting TIMP-1 using small interfering RNA has significant therapeutic potential as an approach to treating keloids 33 . In this study, the expression of TIMP-1 was significantly decreased with Endostar treatments, while the group that did not receive Endostar therapy showed over expression of TIMP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Metaloproteinazy macierzy pozakom贸rkowej i ich substraty [39][40][41] TIMP-2, TIMP-3, TIMP-4) i niespecyficznych inhibitor贸w (伪2-makroglobuliny, 伪1-antytrypsyny, inhibitora plazminogenu 1) [45][46][47][48][49][50][51][52][53][54]. Szczeg贸lne znaczenie w formowaniu keloid贸w maj膮 kolagenaza 1 (MMP-1) i 偶elatynazy (MMP-2 i MMP-9).…”
Section: Czynnik Wzrostu Tkanki 艂膮Cznejunclassified
“…Histological studies revealed that keloid contains overabundant fibroblasts undergoing mitotic division, in which excessive collagen deposition and myxoid stroma can be observed [4]. The etiology of keloid has remarkable similarity with that of tumor, which is often driven by abnormally overexpression of oncogenes, resulting in uncontrolled growth of cells [5][6][7][8]. Indeed, therapies developed to treat keloid such as interferon therapy, intralesional administration of 5-fluorouracil and tamoxifen, excision, and radiation therapy [9][10][11], were originated from cancer therapy.…”
Section: Introductionmentioning
confidence: 99%